Bacterial Microcompartment-Dependent 1,2-Propanediol Utilization Stimulates Anaerobic Growth of Listeria monocytogenes EGDe - Zeng, Zhe; Smid, Eddy J.; Boeren, Sjef; Notebaart, Richard A.; Abee, Tjakko (Frontiers in Microbiology, 2019)
Bacterial microcompartments (BMCs) are proteinaceous organelles that optimize specific metabolic pathways referred to as metabolosomes involving transient production of toxic volatile metabolites such as aldehydes. Previous bioinformatics analysis predicted the presence of BMCs in 23 bacterial phyla including foodborne pathogens and a link with utilization clusters for host-derived substrates such as 1,2-propanediol (Pdu cluster). Although transcriptional regulation of the Pdu cluster and its role in L. monocytogenes virulence in animal models have recently been reported, the experimental identification and the physiological role of BMCs in L. monocytogenes is still unexplored. Here, we ask whether BMCs could enable 1,2-propanediol utilization in L. monocytogenes under anaerobic conditions. Using L. monocytogenes EGDe as a model, we could demonstrate efficient utilization of 1,2-propanediol with concomitant production of 1-propanol and propionate after 24 hours of anaerobic growth, while the utilisation was significantly reduced in aerobic conditions. In line with this, expression of genes encoding predicted shell proteins and the signature enzyme propanediol dehydratase are upregulated more than 20-fold in cells anaerobically grown in Pdu-induced versus non-induced conditions. Additional proteomics analysis confirms the presence of BMC shell proteins and Pdu enzymes in cells that show active degradation of 1,2-propanediol. Furthermore, using transmission electron microscopy BMC structures have been detected in these cells linking gene expression, protein composition and BMCs to activation of the Pdu cluster in anaerobic growth of L. monocytogenes. Studies in defined minimal medium with 1,2-propanediol as sole carbon and energy source showed a significant increase in cell numbers, indicating that the predicted generation of ATP in the conversion of propionyl-phosphate to the end product propionate can support anaerobic growth of L. monocytogenes via 1,2-propanediol utilisation. These findings provide further support for a role of BMC-dependent utilisation of selected substrates including 1,2-propanediol in L. monocytogenes transmission and interaction with the human host.